Physicochemical properties of a novel bioceramic silicone-based root canal sealer - Wei-Jia Lyu; Wei Bai; Xiao-Yan Wang; Yu-Hong Liang (Elsevier, 2022)
Background/purpose: With introduction into endodontics, bioceramic-based sealers have gained considerable popularity for excellent properties. The aim of this study was to investigate the physicochemical properties of a novel bioceramic silicone-based sealer, GuttaFlow Bioseal, and measure heat flow of setting reactions. Materials and methods: Film thickness, flow, working and setting time of Bioseal were compared with other 4 kinds of sealers: iRoot SP, AH Plus, RoekoSeal and GuttaFlow2. Differential scanning calorimetry test was performed to measure heat flow. Results: Bioseal demonstrated the highest film thickness of 44 μm, double to triple that of the other 4 sealers (P < 0.05). The highest flow was detected in iRoot SP and RoekoSeal, with values of 27.35 and 27.20 mm, while GuttaFlow2 and Bioseal had the lowest of 22.31 and 21.43 mm (P < 0.05). For each sealer, working time at 37 °C was shorter than that at 23 °C (P < 0.05). At 37 °C, Bioseal had the shortest working and setting time of 4.5 and 16.3 min, while iRoot SP showed the longest of 105.0 and 571.7 min (P < 0.05). Differential scanning calorimetry test revealed that setting process of all the tested sealers was exothermic. Bioseal reached an exothermic peak at 14 min, with almost 1.5 times peak intensity of GuttaFlow2 and RoekoSeal. Whereas iRoot SP and AH Plus reached an exothermic peak 5 h after mixing, with intensity 1/2 to 2/3 that of Bioseal. Conclusion: The novel bioceramic silicone-based sealer Bioseal showed intense and fast exothermic reactions with characteristic physicochemical properties.